Implementing international watercourses law through the WEF Nexus and SDG : an integrated approach illustrated in the Zambezi River Basin - Yihdego, Zeray; Gibson, Julie (Lawyer) (Brill research perspectives., 2020)
"Implementing International Watercourses Law through the WEF and SDGs: An Integrated Approach Illustrated in the Zambezi River Basin offers an innovative approach to the governance of shared watercourses and the implementation of international water law through the Law, Nexus and Goals (LNG) approach. By looking at policy frameworks such as the WEF nexus and global development agendas such as the SDGs, the monograph provides a method of integration for holistic water governance. In order to demonstrate this approach, a case study of the Zambezi River Basin is used, through which the monograph not only exemplifies the approach taken, but also provides a detailed account of the legal and policy frameworks within the basin"--